A laboratory Study of the allelopathic Efficacy of Aqueous Wheat grain Extracts on Seed Germination and Seedling Growth of Some Weeds spreed in Wheat Fields (Damascus University Journal of agriculture sciences, 2021)
management. A factorial experiment (using RCBD design) with 2 trials was conducted in 2016-2017 in Biological Control Studies and Researches Centre to evaluate the effect of aqueous extract of wheat grains on seed germination and seedling growth of some weeds. The first factor included different aqueous wheat grain extract concentrations (0, 2.5, 5, 10 and 20 percent) and the second factor was the weed species, (Avena sterilis, Hordeum murinum, Galium aparine, Papaver rhoeas, Cirsium arvensis, Sinapis alba, Sisymbrium irio, Diplotaxis erucoides). Whereas wheat extract concentration increased, the inhibitory effect of allelopathic material on seeds germination and seedling growth indices also increased. The results showed that , Sisymbrium irio was the most sensitive species to aqueous wheat grain extract and Papaver rhoeas was the most resistant one. The concentration of 20% has inhibitory effect on all grains and seedling indices, and this indicated the allelopathic properties of wheat grains extract.
Keywords: competition; Allelopathy; Grain Germination; Seedling Growth; Wheat Grains Extract; Weeds Species